Transmission of Ehrlichia canis by Rhipicephalus sanguineus ticks feeding on dogs and on artificial membranes - Fourie, Josephus J.; Stanneck, Dorothee; Luus, Herman G.; Beugnet, Frederic; Wijnveld, Michiel; Jongejan, Frans (Veterinary parasitology, 2013)
A South African strain of Ehrlichia canis was isolated and used to infect a laboratory-bred Beagle dog. Rhipicephalus sanguineus nymphs, which fed on this dog, moulted to adult ticks which carried infection rates of E. canis between 12% and 19% and were used in a series of in vivo and in vitro experiments. Five groups of 6 dogs were challenged with the infected R. sanguineus ticks, which were removed 24h, 12h, 6h or 3h after the ticks had been released onto the dogs. The animals were monitored for fever and thrombocytopenia and were considered infected if they became serologically positive for E. canis antibodies as well as PCR positive for E. canis DNA. Seven dogs became infected with E. canis in the following groups: Group 1 (24h tick challenge) 1 out of 6; Group 2 (12h) 1 of 6; Group 3 (6h) 2 of 6; Group 4 (6h) 2 of 6 and Group 5 (3h) 1 out of 6. Six of those 7 infected dogs developed fever and a significant thrombocytopenia. One dog did not show any symptoms, but seroconverted and was found PCR positive on several occasions. Five additional dogs were PCR positive on one test sample only but were not considered infected because they did not develop any specific E. canis antibodies. In vitro, R. sanguineus ticks attached and fed on bovine blood through silicone membranes with attachment rates up to 72.5% after 24h increasing to 84.2% at 72h. The ticks transmitted E. canis as soon as 8h post application as demonstrated by E. canis DNA found in the nutritive blood medium. In conclusion, transmission of E. canis by R. sanguineus ticks starts within a few hours after attachment, which is earlier than previously thought. These findings underpin the need for acaricides to provide either a repellent, an anti-attachment and/or a rapid killing effect against ticks in order to decrease the risk of transmission of E. canis.